PENINGKATAN KEMAMPUAN MENULIS SISWA PAKET B DAN C MELALUI PELATIHAN TEKNIK PENULISAN ILMIAH - Sumarjaya, I. W.; Joni, M.; Sibarani, J.; Gautama, I. P. W. (Buletin Udayana Mengabdi; Vol 20 No 1 (2021): Buletin Udayana Mengabdi, 2021)
As a nonformal education institution for students that dropped-out of schools, pusat kegiatan belajar masyarakat (PKBM) plays important role in promoting the spirit of lifelong learning and community learning. One of the fundamental components of education, either formal or nonformal, is writing. The ability to write, especially scientific writing, is not an inborn talent but acquired. Results of interview conducted in early February 2019 concluded the followings. First, students are not capable of doing scientific writing correctly. This can be seen from their inability in creating cohesive and coherence sentences. Second, the students seem to lack confidence when participating in writing competition held regularly by Kemdikbud. Finally, the workplace often requires employees to make correspondence and written reports. One way to improve students’ ability to write scientifically is through basic scientific writing workshop. This community service started by giving questionnaires to students which consists of an informal writing about themselves and a scientific writing about social phenomenon. The next step is delivering workshop, giving posttest, and doing workshop evaluation. Based on our evaluation we conclude that the workshop can improve students’ ability to write scientifically.